Combustion characteristics and thermal decomposition mechanism of the flame-retardant cable in urban utility tunnel. (April 2023) - Zheng, Xuezhao; Cai, Guobin; Guo, Jun; Gao, Wenjing; Huang, Yuan; Tong, Xin
Abstract: Although urban utility tunnel act as innovative technique for sustainable development, the cable fire of tunnel should be carefully treated. Extensive studies have usually focused on the combustion or pyrolysis stage of cables by a single test, but comprehensive tests still need to further investigation. Therefore, the cable ignition, expansion charring, pyrolysis and combustion from the macro and micro perspectives were comprehensively explored with cone calorimeter and simultaneous thermal analysis infrared gas chromatography (STA-FTIR-GC/MS). It was found that in addition to the outermost sheath material of the cable, its insulation material and flame retardant material play a non-negligible role in the fire. To more accurately reflect the actual pyrolysis and combustion characteristics of the material, a simplified cable ignition model was established, the combustion laws of typical cables in the urban utility tunnel under different radiation intensities were explored, the quantitative characterization and risk assessment of the toxicity of the gas products were studied. What's more, the pyrolysis characteristics and reaction mechanism of cables under different thermal environments were revealed. The work provides the necessary support for the establishment of database and design standard of fire engineering in urban utility tunnel.